Is “pepectoral edema” a morphologic sign for malignant breast tumors? - Kaiser, Clemens G.; Krammer, Julia; Schönberg, Stefan; Wasser, Klaus (Academic radiology, 2015)
A variety of morphologic and kinetic signs of benign or malignant breast lesions contribute to a final diagnosis and differential diagnosis in magnetic resonance (MR) mammography (MRM). As a new sign, prepectoral edema (PE) in patients without any history of previous biopsy, operation, radiation, or chemotherapy was detected during routine breast MR examinations. The purpose of this study was to retrospectively evaluate the role of this morphologic sign in the differential diagnosis of breast lesions. Between January 2005 and October 2006, a total of 1109 consecutive MRM examinations have been performed in our institution. In this study, only patients who would later be biopsied or operated in our own hospital were included. They had no previous operation, biopsy, intervention, chemotherapy, hormone replacement therapy, or previous mastitis. In total, 162 patients with 180 lesions were included, histologically correlated later-on by open biopsy (124 patients and 136 lesions) or core biopsy (38 patients and 44 lesions). The evaluations were performed by four experienced radiologists in consensus. One hundred eighty evaluated lesions included 104 malignant lesions (93 invasive and 11 noninvasive cancers) and 76 benign lesions. PE was detected in 2.6% of benign lesions (2 of 76), in none of the Ductal cacinoma in situ (DCIS) cases (0 of 11), and in 25.8% of malignant lesions (24 of 93; P < .000). PE was found significantly more frequently in presence of malignant tumors >2 cm in diameter (48.5%, 17 of 35 vs. 13.8%, 8 of 58; P < .001). PE was not statistically associated to malignant tumor type, presence or absence of additional DCIS, and number of lesions. This resulted in the following diagnostic parameters for PE as an indicator for malignancy: sensitivity of 19.3%, specificity of 97.3%, positive predictive value (PPV) of 92.3%, negative predictive value of 48%, and accuracy of 57.7%. In case of occurrence, the “PE sign” seems to be a specific indicator for malignant tumors with a high PPV, independent from its entity.